Characterization of a human placental clearance system to regulate serotonin levels in the fetoplacental unit - Staud, Frantisek; Pan, Xin; Karahoda, Rona; Dong, Xiaojing; Kastner, Petr; Horackova, Hana; Vachalova, Veronika; Markert, Udo R; Abad, Cilia (Reproductive biology and endocrinology, 2023)
BACKGROUND: Serotonin (5-HT) is a biogenic monoamine with diverse functions in multiple human organs and tissues. During pregnancy, tightly regulated levels of 5-HT in the fetoplacental unit are critical for proper placental functions, fetal development, and programming. Despite being a non-neuronal organ, the placenta expresses a suite of homeostatic proteins, membrane transporters and metabolizing enzymes, to regulate monoamine levels. We hypothesized that placental 5-HT clearance is important for maintaining 5-HT levels in the fetoplacental unit. We therefore investigated placental 5-HT uptake from the umbilical circulation at physiological and supraphysiological levels as well as placental metabolism of 5-HT to 5-hydroxyindoleacetic acid (5-HIAA) and 5-HIAA efflux from trophoblast cells. METHODS: We employed a systematic approach using advanced organ-, tissue-, and cellular-level models of the human placenta to investigate the transport and metabolism of 5-HT in the fetoplacental unit. Human placentas from uncomplicated term pregnancies were used for perfusion studies, culturing explants, and isolating primary trophoblast cells. RESULTS: Using the dually perfused placenta, we observed a high and concentration-dependent placental extraction of 5-HT from the fetal circulation. Subsequently, within the placenta, 5-HT was metabolized to 5-hydroxyindoleacetic acid (5-HIAA), which was then unidirectionally excreted to the maternal circulation. In the explant cultures and primary trophoblast cells, we show concentration- and inhibitor-dependent 5-HT uptake and metabolism and subsequent 5-HIAA release into the media. Droplet digital PCR revealed that the dominant gene in all models was MAO-A, supporting the crucial role of 5-HT metabolism in placental 5-HT clearance. CONCLUSIONS: Taken together, we present transcriptional and functional evidence that the human placenta has an efficient 5-HT clearance system involving (1) removal of 5-HT from the fetal circulation by OCT3, (2) metabolism to 5-HIAA by MAO-A, and (3) selective 5-HIAA excretion to the maternal circulation via the MRP2 transporter. This synchronized mechanism is critical for regulating 5-HT in the fetoplacental unit; however, it can be compromised by external insults such as antidepressant drugs.
Keywords: Amines; kyselina hydroxyindoloctová; Kinetics; Fetal development; Hydroxyindoleacetic Acid; serotonin; Pregnancy; těhotenství; Clearance; Homeostasis; Placenta; aminy; placenta; kinetika; lidé; ženské pohlaví; Humans; Female; Serotonin